''توضیح القرآن'' اور ''امداد الکرم ''کے تفسیری محاسن کاتجزیاتی مطالعہ: An Analytical Study of the Exegetical Merits of Tafsīr Tauzīh ul Quran and Tafsīr Imdūd ul Karam (Al-Qamar, 2025)
Holy Quran is the great scripture of Islam, whose commentaries are being written all over the world and every day best of narratives are seen by the reader from its verse and meaning. This is the reason why the need for its interpretation has not decreased in every age, but it is being worked on frequently. In this article, the methods and styles of merits have been explained. There is a Tafsir of Maulana Taqi Usmaani and the second mentioned Tafsir written by Maulana Pirzada Imdad Hussain which is a long and thick volume.
Keywords: Scripture of Islam, Tauzih ul Quran, Imdadulkaram, exegetical merits